Morphometric Analysis of Seagrass Halophila ovalis in the Coastal Waters of Manokwari - Kilmaskossu, Johanis Paulus; Sianipar, Fajar Ria Dwi Natalia; Susanto, Slamet Arif; Lefaan, Paskalina Theresia; Manangkalangi, Emmanuel; Maturbongs, Agatha Cecilia (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Pressure on coastal water conditions in Manokwari caused by human activities can affect the morphometric adaptation of seagrass plants, one of which is Halophila ovalis. The study aimed to analyze the morphometric differences of Halophila ovalis caused by differences in environmental factors on several coastal areas in Manokwari. A total of 20 samples of H. ovalis were taken from each of the beaches studied and then four morphological characters were measured. Morphometric data of H. ovalis between locations were analyzed using analysis of variance (ANOVA), then continued with non-multidimensional scaling (NMDS) analysis. The results showed that there were changes in the morphometrics of H. ovalis from the four research locations. Specifically, it was found that the H. ovalis with the most different morphology came from Rendani Beach. NMDS analysis shows that the morphometrics of H. ovalis on Rendani Beach are separate from from Yenkarwar, Wosi and Saubeba Beaches. The NMDS model was explain 74.19% of the morphometric diversity influenced by environmental parameters such as water temperature, substrate conditions, pH, salinity, and dissolved oxygen levels. We concluded that there had been morphometric changes in the seagrass H. ovalis in several coastal waters in Manokwari.